Diversity and ecological role of Dipterocarpus obtusifolius Teijsm. ex Miq. in Nui Cau - Dau Tieng protection forest, Binh Duong province - Thi Ha, Nguyen; Thi Hanh, Nguyen; Thi Hoa, Nguyen; Van Lam, Nguyen; Thanh Trong, Phan; Chi Thinh, Pham; Van Hop, Nguyen (Journal of Forestry Science and Technology, 2024)
Studying the diversity and ecological role of dominant species provides an important foundation for understanding the influence of dominant species on the diversity and biomass production capacity of plant communities. This study was conducted at the Nui Cau - Dau Tieng Protection Forest Management Board, Binh Duong province, to understand the diversity and ecological role of Dipterocarpus obtusifolius Teijsm. ex Mig. in the ecosystem forests. A total of 19 plots, each 0.1 ha in size (50 m x 20 m), were used for data collection. Trees with a diameter at breast height (dbh) ≥ 6 cm were recorded, including species name, number of individuals, dbh, and overall height. The study employed importance value index analysis (IVI%) and aboveground biomass (AGB) to assess the ecological role of dominant species. Findings revealed that: (1) Communities with dominant species had low species richness and fluctuating diversity levels, (2) The ecological role of dominant species varied across forest states, decreasing from very poor > poor > medium forests, and (3) Increasing IVI% and AGB% of dominant species influenced woody species structure and biomass output in the plant community. This study offers valuable insights to enhance forest management and quality in the area.